Dinamika Cadangan Karbon akibat Perubahan Tutupan Lahan menjadi Lahan Permukiman di Kota Padang Sumatera Barat - Hermon, Dedi (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this study was to analyse the dynamics of carbon stocks changes from land cover into land settlement in the Padang City, West Sumatra. Method to formulate the change of land cover into land settlement in the Padang City is the analysis of Landsat Imagery 5+TM 1988, Landsat 7+ETM Image of 1998 and Landsat 7+ETM Image of 2008. Stratified Sampling Technique was Purpose Composite plot refers to the technique, but in this study carried out modification to the size of the plot which is then converted to the extend of each hectare of land cover. Estimating tree biomass using the equation according Kattering allometric, (2001). The result of the research conducted found that the dynamics of carbon stocks always decline from 1988, 1998 and 2008. This is caused by a reduction in forest area, shrubs, gardens, and fields are consistently due to the increased amount of land used for settlement.